2011
DOI: 10.1073/pnas.1102116108
|View full text |Cite
|
Sign up to set email alerts
|

Drug screening in a zebrafish model of Duchenne muscular dystrophy

Abstract: Two known zebrafish dystrophin mutants, sapje and sapje-like (sap c/100 ), represent excellent small-animal models of human muscular dystrophy. Using these dystrophin-null zebrafish, we have screened the Prestwick chemical library for small molecules that modulate the muscle phenotype in these fish. With a quick and easy birefringence assay, we have identified seven small molecules that influence muscle pathology in dystrophin-null zebrafish without restoration of dystrophin expression. Three of seven candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
176
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(184 citation statements)
references
References 31 publications
(44 reference statements)
6
176
0
Order By: Relevance
“…The sapje dystrophinmutant zebrafish model is an excellent tool for studying dystrophic-muscle and disease progression, as the sapje mutants show dystrophic disease severity and can be analyzed in large numbers in a short period of time. 16,17 The sapje dystrophic zebrafish has a more severe muscle phenotype in which their dorsal muscles progressively waste resulting in significant early lethality as compared with mdx mouse models. [16][17][18] The sapje zebrafish have weakened and degenerating muscle and the majority of mutants (95%) expire by 10 dpf due to the inability to swim and oxygenate their muscles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sapje dystrophinmutant zebrafish model is an excellent tool for studying dystrophic-muscle and disease progression, as the sapje mutants show dystrophic disease severity and can be analyzed in large numbers in a short period of time. 16,17 The sapje dystrophic zebrafish has a more severe muscle phenotype in which their dorsal muscles progressively waste resulting in significant early lethality as compared with mdx mouse models. [16][17][18] The sapje zebrafish have weakened and degenerating muscle and the majority of mutants (95%) expire by 10 dpf due to the inability to swim and oxygenate their muscles.…”
mentioning
confidence: 99%
“…16,17 The sapje dystrophic zebrafish has a more severe muscle phenotype in which their dorsal muscles progressively waste resulting in significant early lethality as compared with mdx mouse models. [16][17][18] The sapje zebrafish have weakened and degenerating muscle and the majority of mutants (95%) expire by 10 dpf due to the inability to swim and oxygenate their muscles. Thus, we chose to utilize the sapje dystrophic zebrafish as a model for analyzing dysregulated dystrophic miRNAs and to expand our previous findings obtained from DMD muscle biopsies.…”
mentioning
confidence: 99%
“…These results indicate that the protein O-mannosyltransferase machinery in zebrafish and humans is conserved and suggest that zebrafish may be useful for functional studies of protein O-mannosylation. More recently, Dr. Kunkel's group has reported that two known zebrafish dystrophin mutants, sapje and sapje-like (sapc/100), represent excellent smallanimal models of human muscular dystrophy 51 . Using these dystrophin-null zebrafish, they have screened the Prestwick chemical library for small molecules that modulate the muscle phenotype in these fish.…”
Section: Studies On Activity-based Profiling With Disease-associatedmentioning
confidence: 99%
“…Due to the fact that most muscular dystrophies result from mutations in proteins that participate in the link between the extracellular matrix and the sarcolemmal cytoskeleton, a common observation at the cellular level is the loss of sacrolemmal integrity 8,9 . This understanding of the primary pathomechanism(s) associated with muscular dystrophies is the product of numerous years of research employing animal model systems 2,[10][11][12][13][14][15] . However, despite advances in the field, there are still limited therapeutic options for treatment or management of the range of dystrophy subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, zebrafish have proven a valuable tool in disease research. The zebrafish model has been used to identify and validate novel human disease causing mutations 16,17 , elucidate uncharacterized disease causing mechanisms 17,18 , and identify novel therapeutic strategies 12,19 . These advances were made, in part, by the canonical strengths of the zebrafish system such as their optical clarity, ease of genetic manipulation, and ability to breed in large numbers 20 .…”
Section: Introductionmentioning
confidence: 99%